Analisis Strategi Marketing Live Shopee Ditinjau Dari Etika Bisnis Islam - siti sopiah, siti; midisen, kisanda (Jurnal Ilmiah Ekonomi Islam, 2024)
E-commerce has become the new favorite in terms of shopping for people around the world, including in Indonesia. Among the various e-commerce that can be accessed in Indonesia, one that is quite well-known and widely used is the Shopee marketplace. Shopee is a shopping application with a marketing strategy through various interesting features, one of which is quite well known is the live streaming feature. Live streaming is a feature that sellers use to create streaming sessions and promote shops & products directly to consumers. Consumers can directly communicate with sellers in real-time to find out more about the product. In this case the author conducted research using a qualitative descriptive method, the researcher described an event or phenomenon that occurred in society related to Shopee's marketing strategy and analyzed this phenomenon in terms of Islamic business ethics, whether the live streaming strategy was in accordance with Islamic business ethics or not. Based on the research results, the marketing strategy through live streaming is in accordance with Islamic business ethics, because live streaming has several regulations that are in accordance with Islamic business ethics. Keywords : Shoppe, Marketing Strategy, Live Streaming, Business Ethics.